New results concerning the identification of neutral inhomogeneities in plane elasticity (Archives of Mechanics - Test, 2006)
Using the concept of a spring-layer (imperfect) interface, we develop the series methods to determine the corresponding interface functions which ensure the (stress) neutrality of an elastic inhomogeneity. We assume that the inhomogeneity occupies a simply-connected domain with a regular boundary and that the inhomogeneity-matrix system is subjected to linear plane deformations. Of particular interest is the fact that the prescribed stress field inside the matrix is assumed to be non-uniform.